2017
DOI: 10.1042/bsr20160557
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy on improving the depression symptoms in patients with diabetes: a meta-analysis of randomized control trials

Abstract: This meta-analysis was performed to evaluate the effect of cognitive behavioural therapy (CBT) in improving the depression symptoms of patients with diabetes. Literature search was conducted in PubMed and Embase up to October 2016 without the initial date. The pooled SMD (standard mean difference) and its 95% confidence interval (CI) were calculated by Revman 5.3. Subgroup analyses were performed by type of diabetes and evaluation criteria of depression. A total of five randomized control trials involving 834 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
(53 reference statements)
0
11
0
2
Order By: Relevance
“…Evidence to date suggests this is the case (8). A meta-analysis found beneficial effects of CBT on depression symptoms in patients with T1DM or T2DM (9). In addition, Li and colleagues further found CBT was effective in reducing depression symptoms, fasting glucose and improving quality of life and anxiety in patients with diabetes in comorbid with depression (10).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to date suggests this is the case (8). A meta-analysis found beneficial effects of CBT on depression symptoms in patients with T1DM or T2DM (9). In addition, Li and colleagues further found CBT was effective in reducing depression symptoms, fasting glucose and improving quality of life and anxiety in patients with diabetes in comorbid with depression (10).…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed nine randomized controlled trials (RCTs) using single CBT as the intervention and found that CBT had short-term and medium-term benefits in improving glycaemic control, and short-term, medium-term, and long-term benefits for depression ( 12 ). Another meta-analysis reviewed five studies on the effect of CBT on depression symptoms in patients with T1DM or T2DM, and demonstrated that CBT can improve depressive mood effectively regardless of the type of diabetes ( 13 ). Li and colleagues conducted a review and meta-analysis including 10 RCTs to explore the effect of CBT for diabetic patients comorbid with depression and found CBT was effective in reducing depression symptoms, fasting glucose and improving quality of life and anxiety in patients with diabetes in comorbid with depression ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that (group)-CBT reduces depressive symptoms in people with diabetes [ 40 ]. We found no effect of group-CBT on the HADS depression scale.…”
Section: Discussionmentioning
confidence: 99%